ОСОБИСТІСНА НАПРАВЛЕНІСТЬ ПІДГОТОВКИ МАЙБУТНІХ ПЕДАГОГІВ В УМОВАХ БЕЗПЕРЕРВНОЇ ОСВІТИ ТА ІНТЕГРАЦІЇ В МІЖНАРОДНУ ОСВІТНЮ СИСТЕМУ (Педагогіка вищої та середньої школи, 2007)
New paradigm of education is expressed in tendency to its «humanization», humanizing of educational sphere, changing of student’s position from an object to a subject of a training process. The problem of quality education, promoted by Bologna Declaration, can't be successfully solved without the transition of the system of continuous educational-discipline training to personal-oriented pedagogical process in Higher School. The article deals with the conditions of transforming social-professional experience into a personal plan of activity.